1798. Phenotypic and Genotypic Impact of Antibiotic Stewardship Intervention on Daptomycin-Nonsusceptible Enterococcus faecium (DNSE) Clinical Isolates. (26th November 2018) - Dhand, Abhay; Lee, Leslie; Feola, Nicholas; Chen, Donald; Dimitrova, Nevenka; Yin, Changhong; Huang, Weihua; Fallon, John; Wang, Guiqing
Abstract: Background: Since its introduction in 2009, use of daptomycin for treatment of enterococcal infections has resulted in the emergence of DNSE. Between 2009 and 2013, daptomycin nonsusceptibility among E. faecium was closely associated with emergence of a unique and dominant clone ST736 in our institution. In 2014, we instituted targeted measures to optimize the use of daptomycin. In this study, we describe the significant phenotypic and genotypic impact of reduced daptomycin use on clinical enterococcal isolates. Methods: Enterococcal clinical isolates were recovered from January 2014 through December 2017. Daptomycin susceptibility was determined by MicroScan WalkAway™ System and confirmed by E -test. Selected DNSE and vancomycin-resistant E. faecium (VREfm) clinical isolates were analyzed by next-generation sequencing (NGS) using the Illumina systems to provide multilocus sequencing type (MLST). Daptomycin utilization data were extracted from pharmacy records. Results: Targeted antibiotic stewardship initiatives consisted of preapproval, daily review for optimization of dose and duration, rapid de-escalation, consideration for appropriate alternative antibiotics for select disease syndromes and stopping of inappropriate daptomycin therapy. Over 4 years, this lead to a 39% reduction in overall use of daptomycin. Besides direct cost saving, this reduced use was associated with significant reduction in daptomycin nonsusceptibility from 12% to 4%, lowering of MIC90 from 8 to 4 μg/mL, and a clonal shift from dominant ST736 to ST117. Conclusion: A targeted antibiotic stewardship initiative to address rising rate of daptomycin nonsusceptibility among E. faecium, resulted in significant phenotypic and genotypic changes among clinical isolates. This study also shows successful integration of NGS in a clinical microbiology lab to validate phenotypic changes of daptomycin nonsusceptibility and to help design future infection control and antibiotic stewardship endeavors. Disclosures: A. Dhand, Merck: Speaker's Bureau, Speaker honorarium. Astellas: Scientific Advisor, Consulting fee.